Strategic Public Participation Based Corruption Prevention in Indonesia - Youngky Fernando; Carl H. D. Steinmetz (The International Journal of Law Review and State Administration, 2025)
Corruption remains a systemic challenge in Indonesia, undermining governance, public trust, and the effectiveness of development programs. This study examines strategies for preventing corruption through public participation as a central component of anti-corruption efforts. Using a qualitative approach, the analysis explores the role of community involvement, transparency mechanisms, and collaborative governance in reducing opportunities for corrupt practices. The findings highlight that public participation strengthens oversight, increases accountability, and fosters a culture of integrity within government institutions. Key strategies include the implementation of participatory budgeting, the use of digital reporting and whistleblowing platforms, community-based monitoring, and the promotion of open data initiatives. Additionally, the study emphasizes the importance of civic education and capacity-building to empower citizens to actively engage in monitoring public services and decision-making processes. The research concludes that corruption prevention in Indonesia requires not only strong legal frameworks but also meaningful, sustained engagement between the government and the public to build a more transparent, accountable, and corruption-resistant governance system.